The relationship between financial inclusion and economic growth: Empirical study from MENA countries - Rabab Jaber Chehayeb; Hanadi Taher (Global Business & Finance Review (GBFR), 2024)
Purpose: The relationship between financial inclusion and economic growth is an intriguing topic that is generating extensive attention among researchers and merits comprehensive investigation. This paper aims to empirically explore this relationship using panel data for 13 Middle Eastern and North African countries spanning the period 2004-2020. The multidimensional index of financial inclusion (encompassing access, usage, and depth) developed by Chehayeb (2024) using a new technique is utilized to generate comprehensive results across countries in emerging economies. Design/methodology/approach: An Autoregressive Distributed Lag (ARDL) regression model is applied to test for co-integration. Vector Auto-Regression (VAR) models and Granger causality tests are employed to investigate the main research questions. Findings: The paper reports an insignificant impact of financial inclusion on economic growth, aligning with the realist perspective of a few studies found in the literature - as opposed to the positivist perspective of most scholars. The results obtained from using the new financial inclusion index highlight the discrepancies and conflicting results among existing studies using multiple proxies of financial inclusion. However, empirical results suggest that there is a unidirectional Granger causality from economic growth to financial inclusion. Findings also reveal the positive impact of economic growth on the access and usage dimensions of financial inclusion, whereas school enrollment, trade openness, and inflation do not appear to be significantly related to financial inclusion. Research limitations/implications: This study is limited to the banking institutions in emerging economies. The study recommends that policymakers and central bank governors in this region utilize the growth of the economy to build an efficient and strong financial system favoring disadvantaged individuals. Future studies on this topic can provide clearer insights with research inclusive of religion levels, political issues, and corruption. Originality/value: This study contributes to the existing literature by using a new measurement of financial in-clusion in studying the relationship between financial inclusion and economic growth.
Keywords: 650; ARDL; Economic growth; Financial inclusion index; Middle East and North Africa; VAR models